Study on the growth of NiSi/SiC core – shell nanowires by hot – wire chemical vapor deposition and its application in supercapacitor / Najwa Hamzan - Najwa , Hamzan (2017)
This work reports on the investigation of NiSi/SiC core – shell nanowires grown by hot – wire chemical vapor deposition technique on crystalline Si (c-Si) and Ni foil substrates. This work was divided into two parts. In the first part, the effect of different substrate temperatures (350⁰C to 530⁰C) on growth and structural properties of the nanowires were studied with SiH4 to CH4 gas flow rates fixed at 1:2. These core-shell nanowires were found to be grown at substrate temperatures above 350⁰C. The nanowires consisted of single crystalline NiSi core and polycrystalline SiC nanocolumn shell. Increase of the substrate temperature enhances the growth of high density vertically aligned nanowires with increment of 2%. The electrochemical properties of NiSi/SiC core-shell nanowires also have been investigated. The specific capacitance of the NiSi/SiC core-shell nanowires obtained from the cyclic voltammetry curve was about 75 mF/cm2, which was nearly three times higher than the intrinsic NiSi nanowires (21 mF/cm2) and four times higher than the blank Ni foil (17 mF/cm2). In the second part, the effects of different CH4 flow rate (0.5 sccm to 3.5 sccm) on the growth, structural and electrochemical properties of the nanowires were investigated. The nanowires were found to be grown at CH4 flow rate above 0.5 sccm. The microstructures studies of these nanowires have demonstrated a single crystalline NiSi core and polycrystalline SiC nanocolumn shell, respectively. In addition, CH4 flow rates also affect the diameter of core and thickness of shell of nanowires. The diameter of core and thickness of shell of nanowires noticeably increased with the increased in CH4 flow rates from 0.5 sccm to 3.5 sccm. The diameter of core of nanowire increased from 19.48 nm to 20.00 nm while thickness of shell of nanowire increased from 54.58 nm to 120.00 nm. The NiSi/SiC core-shell nanowire electrode at 2.0 sccm exhibited an excellent electrochemical performance as compared to other flow rates. The core - shell nanowire electrode has achieved a maximum specific capacitance of 234.13 mF/cm2.